A new alpine autumnal species of the genus Pediasia Hübner, 1825 (Lepidoptera: Crambidae) from Kyrgyzstan - Sinev, Sergey Yu.; Korb, Stanislav K. (Zootaxa, 2024)
A new species, Pediasia gorbunovi sp. nov., is described from Kyrgyzstan, Baidulu Mountains, at Dolon Pass (41°52’40”N, 75°42’11”E, 2790 m altitude). This species is distinguished from its closest relative, P. matricella (Treitschke, 1832), by its lighter wings with a less defined pattern and specific differences in male genitalia, particularly the structure of the aedeagus, saccus, and cucullus. P. gorbunovi is unique in being the only species of the P. matricella group found in high mountain environments.